Effectiveness of discovery learning-based multiple representation module on enhancing the critical thinking skills of the students with high and low science process skills - Muhammad Minan Chusni (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
The study examines the effectiveness of a multiple representation module based on discovery learning in enhancing students' critical thinking. The study used a quasi-experiment design with a 2×2 design analysis. The subjects were 114 students with high and low science process skills from Sleman district's class VII Islamic Junior High Schools. The sample was separated into two groups: a control group that utilized conventional modules and an experimental group that utilized a Discovery Learning-based Multiple Representation module; each sample group was further broken into two groups with high and low science process skills. The test of critical thinking skills was adopted by Facione (2011). Another instrument was an observation sheet to observe science process abilities. The data analysis revealed that implementing the Discovery Learning-based Multiple Representation modules improved students' critical thinking abilities. Not only did student science process abilities influence their critical thinking abilities, but there was also an interaction between the module and student science process abilities.